Estudo DFT da clofazimina e de suas dispersões sólidas com os coformadores ácido P‐aminobenzóico e citosina - SOUSA, Lucas Aires de (2021)
Molecular properties of interest in the development of new drugs, such as thermodynamic, electronic and structural properties, can be determined from the use different theoretical methods. Currently, density functional theory (DFT) has been widely used in the study of chemical systems, due to its good accuracy and relatively low computational cost. Clofazimine (CFZ) presents low water solubility, which reduce its efficiency as a medicine. The problem, however, can be overcome with the preparation of solid dispersions of the drug with coformers with higher water solubility, promoting a significant increase of the bioavailability of the drug in the human organism, contributing to the increase of the efficiency of the drug. In the present work, the DFT was used in the study of properties of CFZ, of properties of the 4-aminobenzoic (PABA) acid and cytosine (CIT) coformers, as well as in the study of ions formed from these compounds and of interactions of CFZ species with ions formed from the coformers. The work was carried out using the DFT functional ωB97x-D and the basis set 6-311++G(d,p) in the study of each of the compounds individually and in the study of interactions in the formation of solid dispersions. Additional calculations were performed with a basis on time-dependent density functional theory (TD-DFT), in the study of electronic absorption energies in the UV-Visible. The solvation effect in each of the systems was studied using the continuum solvation method Integral Equation Formalism Polarizable Continuum Model (IEFPCM). The representations of the chemical structures were treated employing the software ChemCraft and then the geometry optimization calculations were performed, followed by vibrational frequency calculations, using the software Gaussian 16. Each optimized geometry obtained was confirmed as a minimum on the potential energy surface since all the calculated vibrational frequencies are positive. Energy and spatial distribution of the HOMO and LUMO molecular orbitals were calculated, enabling the determination of reactivity parameters of the studied compounds. Electrostatic potential maps and dipole moments were used in determining the preferred sites and orientations of the molecules in the interactions, which contributed in the determination of the most favorable interactions, from the calculation of interaction energy in each case. Spectroscopic data of Fourier Transform Infrared Spectroscopy (FTIR) and Raman were calculated, contributing to the characterization of the systems and to the study of the interactions. The results obtained in the theoretical study confirm the stability of the materials formed from the hydrogen bonds between the species involved in the formation of each of the solid dispersions. Displacements of specific bands in the FTIR and Raman spectra evidenced the interactions between the ions formed from the CFZ and ions formed from PABA, in the case of CFZ-PABA solid dispersion formation, and the interactions between ions formed from CFZ and from CIT, in the case of CFZ-CIT solid dispersion formation. Thus, this study is useful in the potentiation of the use of the leprosy drug CFZ, contributing to the reduction of the needed doses and also of side effects caused by the use of the drug.